1981
DOI: 10.1121/1.385592
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity to pitch distance, particularly in speech

Abstract: The fundamental frequency in speech shows many rapid variations, part of which determine the perceived shape of the pitch contour. This implies that the accuracy with which listeners perceive changes of F0 is more relevant to understanding the perception of intonation than the traditional just noticeable difference of F0 in speech. This study examines the sensitivity to differences in the amount of change of F0, upward (Experiment Ia) and downward (Experiment Ib). Subjects 74 and 104, respectively, with widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(62 citation statements)
references
References 5 publications
2
50
0
5
Order By: Relevance
“…This indicates markedly poorer discriminability than found for steady stimuli. Similarly, 't Hart (1981) found that about a 19% difference was necessary for successive pitch movements in the same direction to be reliably heard as different in extent. Hermes & van Gestel (1991) studied the perception of the excursion size of prominence-lending F0 movements in utterances resynthesized in different F0 registers.…”
Section: The Perception Of Pitchmentioning
confidence: 94%
“…This indicates markedly poorer discriminability than found for steady stimuli. Similarly, 't Hart (1981) found that about a 19% difference was necessary for successive pitch movements in the same direction to be reliably heard as different in extent. Hermes & van Gestel (1991) studied the perception of the excursion size of prominence-lending F0 movements in utterances resynthesized in different F0 registers.…”
Section: The Perception Of Pitchmentioning
confidence: 94%
“…As noted in cross-linguistic surveys of fundamental frequency, the typical pitch range for most human males is about 100 Hz (34)(35)(36). The just-noticeable difference between lexical tones is about 10 Hz (37), and a cross-tone pitch difference of at least 20-30 Hz is considered marginally sufficient to achieve phonemic contrast (38). These figures suggest that languages with more than three level phonemic tones present articulatory and perceptual challenges, a suggestion that is supported by work on the acquisition of tonality (39,40).…”
Section: Significancementioning
confidence: 99%
“…The literature indicates that only pitch differences of more than three semitones can be discriminated reliably in speech [49]. This suggests that misclassifications by less than three semitones would not affect the intended meaning of an intonational change during speech.…”
Section: Standalone Evaluationmentioning
confidence: 99%